PENGARUH STORE ATMOSPHERE DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN MERAWAT KECANTIKAN DI FARINA BEAUTY CLINIC - Dian Nurislah; Cecep Hermana (Prodi Pendidikan Ekonomi-UGJ, 2020)
ABSTRACTMarketing management is the art of selling a product or service and creating, offering and freely exchanging products and services of high value to customers and aims to take advantage of opportunities in the market. This study aims to determine, explain, and analyze the effect of store atmosphere and service quality on decisions to care for beauty at Farina Beauty Clinic Karawang. This type of research is qualitative with 100 respondents who are determined by descriptive and verification methods. Data collection techniques are questionnaires and surveys. The data collection tool uses a questionnaire. The data analysis used is descriptive analysis, data transformation, verification analysis, and path analysis. The results showed that the variable store atmosphere and service quality had a positive and significant effect both partially and simultaneously on the decision to care for beauty at Farina Beauty Clinic. Based on the coefficient of determination, the decision to care for beauty gave a contribution of 0.479 or 47.9% to the variable store atmosphere and service quality. Based on the results of this study, it is suggested to Farina Beauty Clinic to expand the existing parking area and handle consumers swiftly again, so that consumers continue to make repeat purchases at Farina Beauty Clinic. Keywords: Store Atmosphere, Service Quality, Beauty Care Decisions.